Cassava varietal improvement and dissemination in Guangxi - Tien, I-nung; Lee Jun (International Center for Tropical Agriculture, 1998)
The Guangxi Subtropical Crops Research Institute (GSCRI) began their cassava varietal introduction and improvement program in 1981. Since 1985, GSCRI has introduced cassava hybrid seeds as well as promising clones by tissue culture from CIAT/Colombia, from the Thai CIAT program, as well as from other institutes. Through continuous selection and experiments, several promising clones, such as SM1113-1, SM1600-1, CM5443-1, SM1741-8 etc. have been identified, and these have been tested to a certain extent in on-farm trials. Since their release and dissemination these clones have awakened great interest by both farmers and starch factories. Some of them have now spread to other provinces. In China, high yield and high starch content of cassava varieties are still the most important factors in raising the comprehensive benefits resulting from cassava production. This is also the only way to change the stagnated position of cassava production, which in the past increased mainly by increasing the area planted. At the moment, many local governments of the principal cassava growing areas are conscious of this and have started to spend money on the introduction and dissemination of new higher-yielding varieties.